Fish Aquatic Enterprise / Nadzirah Alias - Alias, Nadzirah; Mahmud, Ilyani; Ibrahim, Siti Aisyah; Mat Arip, Norlizawati; Mohd Rani, Nor Jihan (2003)
Five young fresh graduates from MARA University of Technology (UiTM) owned FISH AQUATIC ENTERPRISE who is carrying out a business of tropical fish primarily in 'catfish' and 'red tilapia'. We will commence our business starting on 1st January 2004. It is located at Lot 888,Batu 1 l,Sg.Burung,34250,Tanjung Piandang,Perak. This business has a bright future as there is increasing in population for each year. On the other hand, the supply of fish today cannot meet the demand because of the demand exceeds supply. At the same time, the shortage of supply from supplier is not enough to fulfill the market condition because of problems such as pollution and illegal fisherman. Thus, this establishment of this project is to respond or react with government exclamation, which is to encourage the business of fresh water fish. Besides that, we have chosen this field because there is less involvement among bumiputera to manage this business commercially. That is why we grab this opportunity and work together to prove that bumiputera also may success, just like the non-bumiputera. In starting this business, FISH AQUATIC ENTERPRISE has allocated RM 133,463 as paid-up capital, contribution from all partners. This sum of money vwill bejufly utilized to ensure the stability of company's financial. We hope that, what we have done all this while will come true and will be a good example to pre-entrepreneurs.